Transformasi Digital UMKM Melalui Odoo: Perspektif Sosiologi Agama Pada Praktik Ekonomi Masyarakat Lokal - Natasya Virginia Leuwol; Melda Agnes Manuhutu; Kelvin Kelvin; Etha Etha; Marsya Marsya; Tabita Tabita; Amel Amel; Marcello Marcello; Lulu Jola Uktolseja (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The rapid development of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt to digital systems to increase the efficiency and competitiveness of their businesses. This community service activity aims to support the digitization process at Toko Vyta, an MSME located in Sorong City, Southwest Papua, through the implementation of an Enterprise Resource Planning (ERP)-based information system using the Odoo platform. This activity is carried out with a method that includes direct observation of business processes, interviews with store owners, training on the use of the Odoo system, technical assistance during the implementation process, as well as social and religious reflection to see the impact of digital transformation from the perspective of local community values. The results of the activity show that the implementation of the Odoo system is able to increase efficiency in managing stock of goods, recording sales transactions, and service to customers. Business owners find it helpful in monitoring business activities in real-time, reducing manual recording errors, and increasing service speed. From the perspective of the sociology of religion, the application of digital technology does not contradict the religious and social values of society, but rather strengthens the principles of honest, transparent, and responsible business. Collaboration between students from the Information Systems and Sociology study programs provides an interdisciplinary contribution that enriches understanding of the dynamics of social change in the context of technology. This experience proves that the success of MSME digitalization is not only determined by technological aspects, but also by the ability to integrate social, cultural, and religious approaches in every stage of transformation. Therefore, the digitalization of MSMEs based on local values is an important strategy to be widely implemented in supporting the sustainable economic empowerment of the community.